Internalisation of Anti-Corruption Education Values in Public Elementary Schools in Mataram City, Indonesia - Yorman, Yorman; Suwarni, Suwarni; Jalaludin, Selamat (International Journal of Social Learning (IJSL), 2025)
Anti-corruption education is a strategic effort to build a generation with integrity. This study aims to analyze internalising anti-corruption education values in Public Elementary Schools (Sekolah Dasar Negeri, SDN) in Mataram City from the perspective of social science education. A qualitative approach was used with a case study method involving teachers, students, and principals as informants. The study results indicate that anti-corruption values, such as honesty, responsibility, discipline, and justice, are integrated into the curriculum, teaching methods, and school culture. This internalisation process is strengthened through collaboration between schools, parents, and the community. The main obstacles faced are teachers' limited understanding of anti-corruption education and the lack of support for learning facilities. This study recommends teacher training and strengthening anti-corruption education policies to create an ecosystem supporting anti-corruption character formation.